Receptor-binding domain recombinant protein on alum-CpG induces broad protection against SARS-CoV-2 variants of concern. Issue 26 (9th June 2022) - Pollet, Jeroen; Strych, Ulrich; Chen, Wen-Hsiang; Versteeg, Leroy; Keegan, Brian; Zhan, Bin; Wei, Junfei; Liu, Zhuyun; Lee, Jungsoon; Kundu, Rahki; Adhikari, Rakesh; Poveda, Cristina; et al.
Abstract: We conducted preclinical studies in mice using a yeast-produced SARS-CoV-2 RBD subunit vaccine candidate formulated with aluminum hydroxide (alum) and CpG deoxynucleotides. This formulation is equivalent to the Corbevax TM vaccine that recently received emergency use authorization by the Drugs Controller General of India. We compared the immune response of mice vaccinated with RBD/alum to mice vaccinated with RBD/alum + CpG. We also evaluated mice immunized with RBD/alum + CpG and boosted with RBD/alum. Mice were immunized twice intramuscularly at a 21-day interval. Compared to two doses of the /alum formulation, the RBD/alum + CpG vaccine induced a stronger and more balanced Th1/Th2 cellular immune response, with high levels of neutralizing antibodies against the original Wuhan isolate of SARS-CoV-2 as well as the B.1.1.7 (Alpha), B.1.351 (Beta), B.1.617.2 and (Delta) variants. Neutralizing antibody titers against the B.1.1.529 (BA.1, Omicron) variant exceeded those in human convalescent plasma after Wuhan infection but were lower than against the other variants. Interestingly, the second dose did not benefit from the addition of CpG, possibly allowing dose-sparing of the adjuvant in the future. The data reported here reinforces that the RBD/alum + CpG vaccine formulation is suitable for inducing broadly neutralizing antibodies against SARS-CoV-2, including variants of concern.